Assessing the impact of a new approach to ocean management: Evidence to date from five ocean plans. (June 2015) - Blau, Jason; Green, Lee
Abstract: Previous studies have helped define what good ocean planning (also known as maritime or marine spatial planning) looks like, effective stakeholder engagement, possible conservation and community benefits, and how ocean plans could theoretically cut costs and create economic value. But little evidence has yet been compiled showing the actual results of ocean plans, and whether or not they have delivered on their promise to balance competing interests through a collaborative process that considers environmental concerns. This paper presents an empirical study of five government-approved ocean plans, all of which resulted in broadly shared net benefits. Economically, these five ocean plans delivered on average 60 million per year in value from new industries and retained value in existing industries, although some stakeholders bore losses and government spending did not decrease. Environmentally, planning increased marine protection, ensured industrial uses avoided sensitive habitat, cut carbon emissions, and reduced the risk of oil spills. Socially, marine planning increased broad stakeholder engagement (thus improving design and administration of plans), while building trust that will likely improve sustainable future use of ocean space. Highlights: This paper examines five case studies of in-force ocean plans. Economically, planning delivered net benefits, particularly for offshore wind. Environmentally, planning increased marine protection and spurred wind energy. Socially, planning brought together stakeholders, leading to better outcomes.